Using a deformable discrete-element technique to model the compaction behaviour of mixed ductile and brittle particulate systems - Rajesh Ransing (PHILOSOPHICAL TRANSACTIONS OF THE ROYAL SOCIETY OF LONDON SERIES A-MATHEMATICAL PHYSICAL AND ENGINEERING SCIENCES, 2004)
This paper illustrates the application of a combined discrete- and finite-element simulation to the compaction of assemblies comprising both ductile and brittle particles. Through case studies, the results demonstrate the importance of using a fine mesh on the particle boundary, the effect of fragmentation and its impact on the form of the compression curve, and the effect of inclusion of ductile particles at ca. 25% by volume suppressing brittle failure mechanisms. Although, the calculations can be extended to three dimensions, the computational cost is a current limitation on such calculations. The novelty of this approach is in its ability to predict material yield surfaces for the compaction of a mixture of particles. The initial results are optimistic, but there is a need for model improvement, principally through the ability to capture the random packing of irregular particles since this will eliminate a key problem in defining an initial density for the simulation. The main advantage of this technology is in its ability to minimize the need for expensive triaxial testing of samples to develop the yield-surface history.